2012
DOI: 10.1088/0741-3335/54/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the structure of the plasma-current sheath on the PF-1000 facility

Abstract: The results of studies of the plasma-current sheath structure on the PF-1000 facility in the stage close to the instant of pinch formation are presented. The measurements were performed using various modifications of the calibrated magnetic probes. Studies of the influence of the probe shape and dimensions on the measurements accuracy were done. The current flowing in the converging sheath at a distance of 40 mm from the axis of the facility electrodes was measured. In the optimal operating modes, this current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 34 publications
(38 reference statements)
5
38
0
Order By: Relevance
“…With neon filling, we recorded increase of their length with an average velocity of (2.5 6 0.5) Â 10 5 m/s. If we taken into account (i) the increase of the current and associated magnetic field in internal structures during the formation of plasmoids 24,25 and (ii) the current being carried through these short filaments, we can speculate that they are the traces of some dense points of filaments, (nodules 1 ) which marked the transport of certain filaments from the external current sheath through the cold layer to the internal dense plasmoids to increase the internal closed currents. They should not be the traces of the acceleration of fast ions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…With neon filling, we recorded increase of their length with an average velocity of (2.5 6 0.5) Â 10 5 m/s. If we taken into account (i) the increase of the current and associated magnetic field in internal structures during the formation of plasmoids 24,25 and (ii) the current being carried through these short filaments, we can speculate that they are the traces of some dense points of filaments, (nodules 1 ) which marked the transport of certain filaments from the external current sheath through the cold layer to the internal dense plasmoids to increase the internal closed currents. They should not be the traces of the acceleration of fast ions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Measurements of the current distribution [4][5][6][7] showed that a fraction of the discharge current could form closed loops near the insulator and not be involved in the process of plasma compression. However, it was also shown that, in optimized PF operating modes with a neutron yield as high as 10 10 -10 11 neutrons/shot, the efficiency of current transportation toward the facility axis can reach 100% [8,9]. It should also be noted that inefficient transportation of the discharge current toward the facility axis can be caused, in particular, by the azi-PLASMA DYNAMICS muthal inhomogeneity of the PCS, which has a filamentary structure throughout all discharge stages [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The higher stability of the pinch column at the applied magnet protects both the production of this first neutron pulse and the penetration of the internal discharge current into the dense column [16], [24]. This penetration is realized 200-300 ns after the pinch phase characterized by the peak of the SXRs, as we observe in EI and EIII of Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 52%
“…Fast electrons and ions with an energy of hundred kiloelectronvolts were produced in correlation with the formation and disintegration of these structures. The signals of the magnetic probes confirmed the existence of azimuthal and axial components of the magnetic field in the pinch [16], [17]. The evolution of the spontaneously generated axial magnetic field in the dense toroidal, helical, and plasmoidal structures was described in [18].…”
Section: Puffing Deuterium Compressed By a Neon Plasmamentioning
confidence: 56%
See 1 more Smart Citation